Are We Heading towards a Corporate Tax System Fit for the 21st Century?*. (December 2014) - Devereux, Michael P.; Vella, John
Abstract The most significant problems with the existing system for taxing the profit of multinational companies stem from two related sources. First, the underlying '1920s compromise' for allocating the rights to tax profit between countries is both inappropriate and increasingly hard to implement in a modern economic setting. Second, because the system is based on taxing mobile activities, it invites countries to compete with each other to attract economic activity and to favour 'domestic' companies. The OECD Base Erosion and Profit Shifting (BEPS) initiative essentially seeks to close loopholes rather than to re‐examine these fundamental problems. As a consequence, it is unlikely to generate a stable long‐run tax system. We briefly outline some more fundamental alternative reforms.